Recurrent Occupational Hantavirus Infections Linked to Feeder Rodent Breeding Farm, Taiwan, 2022 - Wang, Kung-Ching; Chang, Chih-Kai; Chang, Shu-Fen; Shu, Pei-Yun; Wang, Hsi-Chieh; Su, Shin-Wei; Lin, Fang-Ling; Wang, Chung-Yu; Su, Chia-ping (Emerging infectious diseases, 2024)
We investigated 2 acute cases and 1 previous case of Seoul hantavirus infection in workers in a feeder rodent breeding farm in Taiwan. Prevalence of hantavirus IgG among the tested feeder rats was 37.5%. Appropriate prevention measures, including using disinfection protocols and personal protective equipment, are crucial to lowering risk.